Hérnia de Littré - Lima Neto,Edgar Valente de (2004)
Littré's hernia is an extremely rare surgical event. It is characterized by the presence of Meckel's diverticulum in the hernial sack. The authors report one case of Littré's hernia in a 42 year-old male who had the diagnosis accomplished in the intraoperative. The diverticulum presented no signs of complications and was treated conservatively , without exeresis.